2018
DOI: 10.1016/j.jmb.2018.05.019
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic and Biochemical Comparison of the Cellular Interaction Partners of Human VPS33A and VPS33B

Abstract: Multi-subunit tethering complexes control membrane fusion events in eukaryotic cells. Class C core vacuole/endosome tethering (CORVET) and homotypic fusion and vacuole protein sorting (HOPS) are two such complexes, both containing the Sec1/Munc18 protein subunit VPS33A. Metazoans additionally possess VPS33B, which has considerable sequence similarity to VPS33A but does not integrate into CORVET or HOPS complexes and instead stably interacts with VIPAR. It has been recently suggested that VPS33B and VIPAR compr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 64 publications
0
23
0
Order By: Relevance
“…Vps33B is a homolog of Vps33A, whereas VIPAS39 shares significant similarity to the C-terminal region of Vps16 (Gissen et al, 2005;Graham et al, 2013). Despite these homologies neither VIPAS39 nor Vps33B are incorporated into HOPS or CORVET (Cullinane et al, 2010;Hunter et al, 2018;Rogerson and Gissen, 2016;Van Der Kant et al, 2015). Recruitment of Vps33A to the human HOPS complex requires the Vps16 residues 642-736 (Graham et al, 2013).…”
Section: The Core Subunits: Late Endosome-lysosome Fusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Vps33B is a homolog of Vps33A, whereas VIPAS39 shares significant similarity to the C-terminal region of Vps16 (Gissen et al, 2005;Graham et al, 2013). Despite these homologies neither VIPAS39 nor Vps33B are incorporated into HOPS or CORVET (Cullinane et al, 2010;Hunter et al, 2018;Rogerson and Gissen, 2016;Van Der Kant et al, 2015). Recruitment of Vps33A to the human HOPS complex requires the Vps16 residues 642-736 (Graham et al, 2013).…”
Section: The Core Subunits: Late Endosome-lysosome Fusionmentioning
confidence: 99%
“…As discussed in the context of the Vps3-Vps8 recycling pathway, the CCC and Retriever complexes are involved in the sorting of cargoes bearing an NPxY/NxxY motif, including integrins, into a specialized endosomal recycling pathway (McNally et al, 2017). Recent studies have shown that Vps33B interacts with CCDC22 of the CCC complex (Hunter et al, 2018), binds integrin β subunits (Xiang et al, 2015) and is required for integrin recycling (Rogerson and Gissen, 2018). This functionally links Vps33B to the CCC and Retriever complexes and raises the question of whether Vps33B can recruit the CCC complex to Rab11-positive recycling endosomes for the formation of recycling tubules.…”
Section: Chevi: Recycling Bacterial Clearance and Biogenesis Of Lysomentioning
confidence: 99%
See 2 more Smart Citations
“…CHEVI is associated with both conserved, lineage-and tissue-specific structures, e.g., α-granules and lamellar bodies, which are mammalian platelet-specific and keratinocyte-specific lysosome-related organelles (LROs) (Bem et al, 2015;Dai et al, 2016;Lo et al, 2005;Rogerson and Gissen, 2018). A similar configuration pertains for Drosophila Vps16B and Vps33B, which also form a novel complex (Cullinane et al, 2010;Gissen et al, 2004;Hunter et al, 2018;Pulipparacharuvil et al, 2005;Tornieri et al, 2013). Further, HOPS or CORVET subunits may function in stable sub-complexes.…”
Section: Introductionmentioning
confidence: 99%